Spatial connectivity of aquatic macrophytes and flood cycle influence species richness of an ant community of a Brazilian floodplain - Marlon C. Pereira; Jacques H. C. Delabie; Yzel Rondon Súarez; William Fernando Antonialli-Jr. (Sociobiology)
Despite the environmental and economic importance of Pantanal, there are few studies quantifying the influence of sazonality and spatial variation on biological diversity in this ecosystem. In this context, the present work aimed to study the assemblage of ants associated with macrophytes during the flood and dry period of Paraguay river, in marginal environments in the Pantanal of Porto Murtinho, Mato Grosso do Sul. We observed a wide variation in the temporal distribution of the diversity of the assemblages of ants, since from 37 species, 36 occurred in the dry and 20 in the flood period. Of the total of macrophyte species observed, in only 12.5% we found a more specific correlation with ants that were nesting in spaces provided by plants representing a total of 10.52% of the species analized.